Sobre a regularidade de Castelnuovo-Mumford de arranjos de subespaços lineares no espaço projetivo n-dimensional - Sousa, Roger Oliveira (2015)
The objetive of this work is study the behavior of the Castelnuovo-Mumford regularity in arrangements of linear subspaces in projetive spaces, for this, we use Jessica Sidman and Harm Derksen article of title "A sharp bound for the Castelnuovo-Mumford regularity of subspace arrengements". At first, we give some preliminary notions and present auxiliary results. In a second moment, we define the main objects of this work proof the main results and give a example which show that the bound is sharp.